Impact of a Single Nucleotide Polymorphism on the 3D Protein Structure and Ubiquitination Activity of E3 Ubiquitin Ligase Arkadia - Birkou, Maria; Raptis, Vasilios; Marousis, Konstantinos D.; Tsevis, Athanasios; Bourikas, Kyriakos; Bentrop, Detlef; Episkopou, Vasso; Spyroulias, Georgios A. (Frontiers in Molecular Biosciences, 2022)
Single nucleotide polymorphisms (SNPs) are genetic variations which can play a vital role in the study of human health. SNP studies are often used to identify point mutations that are associated with diseases. Arkadia (RNF111) is an E3 ubiquitin ligase that enhances transforming growth factor-beta (TGF-β) signaling by targeting negative regulators for degradation. Dysregulation of the TGF-β pathway is implicated in cancer because it exhibits tumor suppressive activity in normal cells while in tumor cells it promotes invasiveness and metastasis. Τhe SNP CGT>TGT generated an amino-acid (aa) substitution of Arginine 957 to Cysteine on the enzymatic RING domain of Arkadia. This was more prevalent in a tumor than in a normal tissue sample of a patient with colorectal cancer. This prompted us to investigate the effect of this mutation in the structure and activity of Arkadia RING. We used nuclear magnetic resonance (NMR) to analyze at an atomic-level the structural and dynamic properties of the R957C Arkadia RING domain, while ubiquitination and luciferase assays provided information about its enzymatic functionality. Our study showed that the R957C mutation of R957C changed the electrostatic properties of the RING domain however, without significant effects on the structure of its core region. However, the functional studies show that the R957C Arkadia exhibits significantly increased enzymatic activity supporting literature data that Arkadia within tumor cells promotes aggressive and metastatic behavior.